2017
DOI: 10.4236/ojog.2017.79100
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Utilisation of Emergency Contraception Pills among Female Undergraduate Students at the University of Nairobi, Kenya

Abstract: Background: Emergency Contraception (EC) is used after unprotected sexual intercourse, following sexual abuse, misuse of regular contraception or non-use of contraception. Seventeen percent of pregnancies in Kenya are unintended, potentially leading to unsafe abortion that contributes to the high maternal mortality rate in Country. According to 2016 Kenya Demographic and Health Survey (KDHS), the maternal mortality ratio was 362 maternal deaths per 100,000 live births. Female students in University or College … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 11 publications
3
13
4
Order By: Relevance
“…The review revealed that students age less than 20 were less likely to practice emergency contraceptives [ 19 – 22 , 27 ]. This finding was consistent with the finding of a study conducted in Kenya [ 28 ]. This might be related to, less exposure for sexual experience due to less adaptiveness for the environment and less sexual experience of their peer.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The review revealed that students age less than 20 were less likely to practice emergency contraceptives [ 19 – 22 , 27 ]. This finding was consistent with the finding of a study conducted in Kenya [ 28 ]. This might be related to, less exposure for sexual experience due to less adaptiveness for the environment and less sexual experience of their peer.…”
Section: Discussionsupporting
confidence: 94%
“…This systematic and meta-analysis revealed that the overall prevalence of emergency contraceptive practice during the period studied in Ethiopia was 34.5% [95% CI [20.8, 48.2%]. This study is higher than findings from South African university students, 28% [ 10 ], Cameroon, 7.4% [ 11 ] Kenya, 20.2% [ 28 ], Kampala, 7.4% [ 29 ] Hong Kong, 12.9% [ 30 ]. The variation could be due to easy availability of the drug without prescriptions but lower than a study conducted in Federal Polytechnic Kaduna, Nigeria 38% [ 12 ], Ghana 41% [ 31 ].…”
Section: Discussionmentioning
confidence: 85%
“…In this study, more than half (51.4%; 95% CI, 45.1–57.7%) of the respondents had awareness of ECP. This is lower than the reports of previous studies conducted in different universities of Ethiopia (67% to 95.9%) 26–28 , 30 , 31 and Kenya (86.4%) 12 but much higher than that of a Nigerian university (14.6%). 13 It is consistent with results from a South African university (49.8%).…”
Section: Discussioncontrasting
confidence: 71%
“…2–4 , 9 For instance, certain multinational analysis of ECP use indicated that the proportions of ECP use varies from below 0.1% in Chad to 12% in Colombia. 10 Other studies also reported that the magnitude of ECP practice among female university students varies across countries in Africa: 21.2% in South Africa, 11 20% in Kenya 12 and 15.2% in Nigeria. 13 The Ethiopian Demographic Health Survey of 2016 (EDHS 2016) reports showed that practice and knowledge of emergency contraception was 4% and 19%, respectively among Ethiopian women aged 15–49.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies identi ed different sources providing information on emergence contraceptive. Accordingly, the most commonly stated sources of information included mass media, books/magazine and friend/partner (10,11) These evidences clearly show that method mix (formal education, combination of mass media and internet) has to be used to make emergence contraceptive information as widely disseminated as possible so as to increase awareness of youth and adolescence in universities as well as community at large.…”
Section: Discussionmentioning
confidence: 99%